PEMIKIRAN SUFISTIK MUHAMMAD SHALIH AL-SAMARANI - In’amuzzahidin, M. (WALISONGO, 2012)
Abstract Â  The ideas of sufism of Muhammad Shalih al-Samarani in Matn al-á¸¤ikam and MajmÅ«âat al-SharÄ«âah al-KÄfiyah li âl-âAwÄm is still rarely studied by researcher. The sufism of Muhammad Shalih al-Samarani emphasizes on implementing islamic doctrine with sincerity and submition to God. Muhammad Shalih bases his sufism on practical (sunniamali) sufism. He reject philosophical (falsafi) sufism, embraced by especially lay people. Â  *** Ide tentang sufismeMuhammad Shalih al-Samarani dalam Matn al-á¸¤ikam dan MajmÅ«âat al-SharÄ«âah al-KÄfiyah li âl-âAwÄm masih jarang dikaji. Sufisme Muhammad Shalih alSamarani menekankan implementasi doktrin Islam dengan ketundukan kepada Tuhan. Muhammad Shalih mendasarkan sufismenya pada sufisme praktis (sunni-amali). Dia menolak sifisme filosofis (falsafi), yang khususnya dianut oleh masyarakat awam. Â  Keywords: faá¸l, irÄdah, tadbÄ«r, ikhlas, zuhud, waá¸¥dat al-wujÅ«d, khushuâ